Change from Hybrid to Fully Minimally Invasive and Robotic Esophagectomy is Possible without Compromises - Grimminger, P. P.; Tagkalos, E.; Hadzijusufovic, E.; Corvinus, F.; Babic, B.; Lang, H. (The Thoracic and Cardiovascular Surgeon, 2019)
Background The incidence of esophageal carcinoma is increasing in the western world, and esophageal resection is the essential therapy. Several studies report advantages of minimally invasive esophagectomies (MIEs) versus conventional open procedures (OPs). The benefits of the use of fully MIE or robot-assisted MIE (RAMIE) compared with the hybrid approaches (laparoscopic gastric preparation and open transthoracic esophagectomy) remain unclear.Methods Between July 2015 and August 2017, the data of 75 patients with esophageal carcinoma were prospectively registered. Of the 75 patients, 25 treated with a hybrid MIE (hybrid), 25 with total MIE (MIE), and 25 with RAMIE. All patients were operated by the same specialized surgeon in our center with an identical anastomotic technique (circular stapler).Results The overall 30- and 90-day mortality rates were 0 and 1.33% (1/75), respectively. Total hospital stay (p = 0.262), intensive care unit stay (p = 0.079), number of resected lymph nodes (p = 0.863), and R status (p = 0.132) did not differ statistically between the groups. However, pneumonia and wound infections occurred significantly and more frequently in the hybrid group compared with the minimally invasive groups (MIE and RAMIE) (p = 0.046 and p = 0.003, respectively).Conclusion Comparable results regarding morbidity and short-term outcome could be achieved in the MIE and RAMIE groups compared with the hybrid group. The data indicate that the learning curve is low in surgeons changing the technique form hybrid esophagectomy to fully MIE. Additionally, the total minimally invasive approaches seem to be associated with a low incidence of complications such as pneumonia and wound infections.
Keywords: Robotics; minimally invasive surgery; port access; minithoracotomy; surgical equipment; esophageal surgery